Pulmonary vein isolation does not alter cardiovascular afferent autonomic reflexes in atrial fibrillation - Varun Malik; Adrian D. Elliott; Gijo Thomas; Bradley Pitman; John L. Fitzgerald; Glenn D. Young; Leonard F. Arnolda; Dennis H. Lau; Prashanthan Sanders (Journal of Arrhythmia, 2025)
Abstract Background Pulmonary vein isolation (PVI) remains the cornerstone of atrial fibrillation (AF) ablation. We previously demonstrated abnormal cardiac volume‐sensitive reflexes (whose receptors are co‐located in veno‐atrial tissue) in AF patients. Whether PVI disrupts afferent nerves is unknown. Objectives Evaluate whether PVI disrupts afferent volume‐sensitive reflexes. Methods We consecutively studied autonomic reflexes in AF patients undergoing PVI, repeating the study post‐PVI, if AF‐free >6 months. We excluded patients with AF recurrence/procedural complications, allowing repeat procedures. We measured beat‐to‐beat mean arterial pressure (MAP) and heart rate (HR) continuously during low‐level Lower Body Negative Pressure (LBNP), at 0, −20 and −40 mmHg (predominantly testing volume baroreceptors); Valsalva reflex (predominantly arterial baroreceptors); and Isometric Handgrip reflex (IHR, both). LBNP produces reflex vasoconstriction, evaluated from forearm blood flow (FBF ∝ 1/vascular resistance). Results 18 patients were studied pre‐PVI; n = 9 completed both visits. Mean age was 64 ± 3 years (78% male); BMI 28 ± 1 kg/m2; LA size 37 ± 2 mL/m2; and left ventricular function 65 ± 3%. Despite alterations in heart rate variability (HRV), there was no difference in IHR, Valsalva, or LBNP responses pre‐ versus post‐PVI. During LBNP, MAP decreased slightly both pre‐ (−1.6 ± 3%) and post‐PVI (−2.8 ± 1.8%); p = .7. HR increased similarly (p = .7) pre‐ (10.6 ± 6.4%) and post‐PVI (7.2 ± 1.5%). FBF response was unchanged (p = .8). Resting (arterial) baroreflex sensitivity was unaltered. Conclusion PVI does not impair cardiovascular reflexes involving afferent baroreceptors, suggesting HRV changes reflect efferent modulation or ablation adequacy rather than afferent disruption. Whether disrupting sino‐atrial efferent nerves represents a marker of adequate ablation or influences PVI outcomes requires evaluation.